Penyuluhan: Pemanfaatan Pelayanan Kesehatan yang Optimal pada Penyakit Langka - Dyah Ayu Sulistyaning Cipta; Trio Ageng Prayitno; Era Dewi Kartika (JPM PAMBUDI, 2019)
The purpose of holding counseling in the form of a talkshow with the theme Role of Families in Bridging the Affect of Rare Disease with Optimal Health Services is to increase public awareness of children with special needs, especially rare diseases, and foster parents' enthusiasm in bridging children with rare diseases with optimal health services Thus, it is expected that children with special needs will get support both physically and psychologically, so that they can develop their own potential, grow to become empowered individuals, and get the best quality of life. This event is also a form of our support for parents with children with special needs, especially with rare diseases. This ceremony was held at the 6th Floor Hall of RSI Aisyiyah Malang on Saturday, March 2, 2019.